Effects of season on bull sperm quality in thawed samples in northern Spain. (11th March 2017) - Sabés‐Alsina, M.; Johannisson, A.; Lundeheim, N.; Lopez‐Bejar, M.; Morrell, J. M.
Abstract : The aim of the present study was to evaluate the possible effects of climate factors on sperm quality of Holstein dairy bulls housed in northern Spain. Semen samples from 11 Holstein dairy bulls were collected and cryopreserved in winter, spring and summer. Sperm quality parameters such as motility, morphology, plasma membrane integrity, acrosome status, mitochondrial membrane potential, DNA fragmentation index and reactive oxygen species were assessed. Samples collected in spring showed higher mean values of total and progressive motility compared with samples collected in winter. Mean values of average path velocity and straight‐line velocity were higher in spring than in summer. The proportion of viable spermatozoa was higher in spring than in winter as was the proportion of viable spermatozoa with non‐reacted acrosome. The proportion of live cells that were not producing superoxide or hydrogen peroxide was higher in samples collected in spring than in winter. No differences were found in sperm morphology or the DNA fragmentation index among seasons. In conclusion, results suggest that sperm quality of bulls housed in northern Spain is affected by season. Samples collected in spring appear to have better sperm quality than samples collected in other seasons.